Stereotypes on the Borderline: Hungarians as Otherness in Croatian Literature and Culture - Rafolt, Leo (2010)
The article explores the concepts of otherness in Croatian and Hungarian cross-cultural perspective, primarily on the material of early modern and 19th century literary culture.
Projekt MZOS
ENG